PENERAPAN PENDEKATAN PEMBELAJARANCONTEXTUAL TEACHING AND LEARNING(CTL) DALAM UPAYAPENINGKATAN KETERAMPILAN BERPIKIR KRITIS - Devi Lestari; Saiful Prayogi; Bq Azmi Syukroyanti (Lensa: Jurnal Kependidikan Fisika, 2017)
This research aim to increase students’ critical thinking skill by using Contextual Teaching and Learning (CTL). This research is class room action research which use the quantitative approach. Subject of the research is VIII grade students’ and object of the research is students’ critical thinking skill in SMPN 5 Narmada. The instrument of the research is the critical thingking skill test. The data collection technique in this research is test and observation sheet, the test is used to measure the critical thingking skill whether the observation sheet is used to measure students’ and teacher activity. The result of research shows that the application of Contxtual Teaching and Learning (CTL) approach can increase students’ critical thinking skill. This can be seen from the data analysis result where the I cyrcle reach 49,91 and the II cyrcle reach 80,00 which involve in critical category.